An exploratory study on blind users' mental model in computer accessibility - Muniandy, M.A.P. (Asian Research Publishing Network, 2014)
The growing needs in the area of HCI has led to many new researches focusing on user-centric design, investigating the problems faced by a computer user and ways to produce an effective yet efficient design. Often, designers need to acquire the knowledge and the experience of the users to produce a good interface design. This can be referred as a wise exploitation of user's mental model. The paper serves as a preliminary study which explores the mental model of blind users as a contribution in improving the accessibility of computer applications. Based on the blind user's perception, imagination and interpretation, the study indicates that touch sensation plays an important role in improving the representation of a computer application to them. Associating touch sensation with information familiar to the blind users enhances the learning process. Â© 2006-2014 Asian Research Publishing Network (ARPN).